Expansion of effector memory Vδ2neg γδ T cells associates with cytomegalovirus reactivation in allogeneic stem cell transplant recipients - Huang, Yiwen; Jiang, Cen; Zhu, Jiacheng; Lin, Lin; Mao, Minjing; Yin, Tong; Cai, Gang (Frontiers in Immunology, 2024)
Background: Cytomegalovirus (CMV) reactivation is a significant concern following allogeneic stem cell transplantation. While previous research has highlighted the anti-CMV reactivation effect of γδ T cells in immunocompromised transplant patients, their characterization in recipients at high risk of CMV reactivation remains limited.Methods: This study focused on D+/R+ recipients (where both donor and recipient are CMV seropositive) at high risk of CMV reactivation. We analyzed 28 patients who experienced CMV recurrence within 100 days post-allogeneic hematopoietic stem cell transplantation, along with 36 matched recipients who did not experience CMV recurrence. Clinical data from both groups were compared, and risk factors for CMV reactivation were identified. Additionally, CMV viral load was measured, and flow cytometric analysis was conducted to assess changes in peripheral blood γδ T cell proportions, subpopulation distribution, and differentiation status. We also analyzed the CDR3 repertoire of the TCR δ chain in different γδ T cell subsets. Functional analysis was performed by measuring the lysis of CMV-infected cells upon stimulation.Results: CMV reactivation post-transplantation was associated with acute graft-versushost disease (aGvHD) and reactivation of non-CMV herpesviruses. Notably, CMV reactivation led to sustained expansion of γδ T cells, primarily within the Vδ2 neg γδ T cell subpopulation, with a trend towards differentiation from Naive to effector memory cells. Analysis of the δ chain CDR3 repertoire revealed a delay in the reconstitution of clonal diversity in Vδ2 neg γδ T cells following CMV reactivation, while Vδ2 pos T cells remained unaffected. Upon stimulation with CMV-infected MRC5 cells, the Vδ2 neg γδ T cell subpopulation emerged as the primary effector cell group producing IFN-γ and capable of lysing CMV-infected cells. Moreover, our findings suggest that NKG2D is not necessary involved in Vδ2 neg γδ T cell-mediated anti-CMV cytotoxicity.This study provides novel insights into the role of γδ T cells in the immune response to CMV reactivation in transplantation recipients at high risk of CMV infection. Specifically, the Vδ2 neg γδ T cell subpopulation appears to be closely associated with CMV reactivation, underscoring their potential role in controlling infection and reflecting CMV reactivation in HSCT patients.